2019
DOI: 10.1155/2019/7069757
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Water Immersion on the Adhesion between Adhesive Layer and Concrete Block

Abstract: The effectiveness of load transfer in the CFRP-adhesive-concrete system highly relies on the integrity of the interfacial bond between adhesive layer and concrete. In the present paper, the effects of water immersion on the mode I fracture energy of the adhesion between CFRP adhesive and concrete were investigated experimentally and numerically. Four-point bending test was conducted to measure the mode I fracture energy of the interfacial layer between adhesive and concrete. The moisture content distribution a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Moreover, experimental studies have confirmed this conclusion. As an example, Shi et al [35] discovered that the deterioration of the peeling fracture energy was proportional to the amount of moisture at the bonding-layer-concrete interface.…”
Section: Analysis Of Interaction Energymentioning
confidence: 99%
“…Moreover, experimental studies have confirmed this conclusion. As an example, Shi et al [35] discovered that the deterioration of the peeling fracture energy was proportional to the amount of moisture at the bonding-layer-concrete interface.…”
Section: Analysis Of Interaction Energymentioning
confidence: 99%